The Role of Sorting Nexin 17 in Cardiac Development - Wu, Yufei; Zhou, Yaqun; Huang, Jian; Ma, Ke; Yuan, Tianyou; Jiang, Yong; Ye, Maoqing; Li, Jun (Frontiers in Cardiovascular Medicine, 2021)
Sorting nexin 17 (SNX17), a member of sorting nexin (SNX) family, acts as a modulator for endocytic recycling of membrane proteins. Results from our previous study demonstrated the embryonic lethality of homozygous defect of SNX17. In this study, we investigated the role of SNX17 in rat fetal development. Specifically, we analyzed patterns of SNX17 messenger RNA (mRNA) expression in multiple rat tissues and found high expression in the cardiac outflow tract (OFT). This expression was gradually elevated during the cardiac OFT morphogenesis. Homozygous deletion of the SNX17 gene in rats resulted in mid-gestational embryonic lethality, which was accompanied by congenital heart defects, including the double-outlet right ventricle and atrioventricular and ventricular septal defects, whereas heterozygotes exhibited normal fetal development. Moreover, we found normal migration distance and the number of cardiac neural crest cells during the OFT morphogenesis. Although cellular proliferation in the cardiac OFT endocardial cushion was not affected, cellular apoptosis was significantly suppressed. Transcriptomic profiles and quantitative real-time PCR data in the cardiac OFT showed that SNX17 deletion resulted in abnormal expression of genes associated with cardiac development. Overall, these findings suggest that SNX17 plays a crucial role in cardiac development.